An atlas of the protein-coding genes in the human, pig, and mouse brain - Sjöstedt, Evelina; Zhong, Wen; Fagerberg, Linn; Karlsson, Max; Mitsios, Nicholas; Adori, Csaba; Oksvold, Per; Edfors, Fredrik; Limiszewska, Agnieszka; Hikmet, Feria; Huang, Jinrong; Du, Yutao; et al. (Science (American Association for the Advancement of Science), 2020)
The brain, with its diverse physiology and intricate cellular organization, is the most complex organ of the mammalian body. To expand our basic understanding of the neurobiology of the brain and its diseases, we performed a comprehensive molecular dissection of 10 major brain regions and multiple subregions using a variety of transcriptomics methods and antibody-based mapping. This analysis was carried out in the human, pig, and mouse brain to allow the identification of regional expression profiles, as well as to study similarities and differences in expression levels between the three species. The resulting data have been made available in an open-access Brain Atlas resource, part of the Human Protein Atlas, to allow exploration and comparison of the expression of individual protein-coding genes in various parts of the mammalian brain.